2021
DOI: 10.3390/ani11020352
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Improving the Metabolic Health of Dairy Cows during the Transition Period

Abstract: The peripartum period of a dairy cow is characterized by several physiological and behavioral changes in response to a rapid increase in nutrient demands, to support the final stages of fetal growth and the production of colostrum and milk. Traditionally, the transition period is defined as the period 3 weeks before and 3 weeks after parturition. However, several researchers have argued that the transition period begins at the time of dry-off (~60–50 days prior to calving) and extends beyond the first month po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 133 publications
0
24
0
2
Order By: Relevance
“…In high-yielding dairy cows, the transition from gestation to intensive lactation is often marked by significant physiological changes that make the animals vulnerable to different diseases during the early lactation period [22]. This is also influenced by the lack of sufficient feed intake, which often does not supply the energy needed for maintaining basal metabolism and milk production, thereby causing NEB [2].…”
Section: Discussionmentioning
confidence: 99%
“…In high-yielding dairy cows, the transition from gestation to intensive lactation is often marked by significant physiological changes that make the animals vulnerable to different diseases during the early lactation period [22]. This is also influenced by the lack of sufficient feed intake, which often does not supply the energy needed for maintaining basal metabolism and milk production, thereby causing NEB [2].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports suggested that nutrient partitioning and other metabolic activities are the essential physiological processes that subsequently help in subclinical ketosis (SCK) prevention (3) and improving cow's health during the transition and early lactation periods of dairy cattle. In general, the fatty acids, blood metabolites and GH directly or indirectly influence animals in terms of growth, reproduction, welfare condition, during the transition and early lactation periods (4)(5)(6)(7). During the early lactation period, dairy cows experience tremendous physiological and metabolic changes (8)(9)(10), accompanied by fetal development, milk production, high energy intake and a negative energy balance (NEB).…”
Section: Introductionmentioning
confidence: 99%
“…Організм намагається ліквідувати гіпоглікемію за рахунок глюконеогенезу. Гіперсекреція глюкокортикоїдів спричиняє мобілізацію жирів із депо, які потрапляючи у печінку, викликають жирову інфільтрацію гепатоцитів (Morris et al, 2009;Caixeta & Omontese, 2021). Такі зміни в організмі корів є основними в патогенезі жирової дистрофії печінки.…”
Section: рис 2 вміст сечовини у сироватці крові корівunclassified